Development of E-Module Based on Socio Scientific Issues Integrated with Islamic Values to Improve Critical Thinking Skills and Scientific Literacy in Biotechnology Material - Arimbi Rizki Hardin; Hindriana, Anna Fitri; Abidin, Zaenal (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Sukabumi, 2025)
Background: The weakness in students’ critical thinking skills is reflected in their tendency to passively accept information without considering broader aspects, such as scientific issues and religious values. Furthermore, the application of biotechnology often triggers controversy within society, highlighting the urgent need for strong scientific literacy skills. One contributing factor to this issue is the limited availability of teaching materials that integrate socio-scientific issues (SSI) with Islamic values, which continues to pose a challenge for educators. Methods: This study employed the ADDIE Research and Development (R&D) model, encompassing the stages of analysis, design, development, implementation, and evaluation. The effectiveness of the developed e-module was evaluated during the final stage by calculating the N-gain score. Data analysis was conducted using the SPSS software. The findings revealed that the average N-gain score in the experimental class was 0.33, compared to 0.22 in the control class. Additionally, the scientific literacy score in the experimental class was 41.88, while the control class scored 30.67 Results: The results showed an average N-gain score for the experimental class of 0.33 while the control class was 0.22. And the acquisition of scientific literacy scores in the experimental class was 41.88 while the control class was 30.67. Conclusion: These results indicate that the SSI-based e-module integrated with Islamic values has a positive effect on enhancing students’ critical thinking skills and scientific literacy.